Article RETRACTED due to malpractice Impact of Emotional Regulation Training, Physical Literacy, and Composite Exercise Programs on Psychosocial Well-Being among Juvenile Female: An Experimental Study - Manhas, Komal (Retos, 2026)
Abstract Background: Adolescence is a vital developmental stage characterized by emotional, social, and psychological changes. Juvenile females in institutional settings frequently experience higher levels of stress, emotional instability, and psychological difficulties. Interventions such as emotional control training, physical literacy activities, and structured exercise programmes may benefit their mental health and overall well-being. Aim: This study aims to explore in depth the effects of emotional regulation techniques, physical literacy, and composite training programs on the psychosocial well-being of female juveniles. Methodology: A randomized experimental design with pre-test and post-test phases was adopted. Initially, 80 juvenile females aged 13-18 years were recruited from Gandhi Vanita Ashram in Jalandhar (Punjab); however, only 60 participants finished the study due to health concerns and a lack of motivation. Participants were placed into three experimental groups and one control group (15 each). The experimental groups participated in a 12-week intervention program with four sessions each week. The data were analysed using descriptive statistics, the t-test, and the ANCOVA. Results: At the 0.05 level of significance, all experimental groups showed a significant decrease in adolescent girls’ health concerns when compared to the control group. The physical literacy group performed somewhat better than the emotional control and composite training groups. Conclusion: The findings indicate that structured psychological and physical training programs effectively improve the psychosocial well-being and health of juvenile females and can be used as therapies to manage adolescent girls’ health issues. Keywords: adolescent girls’ health problems; composite training; emotional regulation; juvenile females; physical literacy.